Determining the mechanical properties of a radiochromic silicone-based 3D dosimeter. (14th June 2017) - Kaplan, L P; Høye, E M; Balling, P; Muren, L P; Petersen, J B B; Poulsen, P R; Yates, E S; Skyt, P S
Abstract: New treatment modalities in radiotherapy (RT) enable delivery of highly conformal dose distributions in patients. This creates a need for precise dose verification in three dimensions (3D). A radiochromic silicone-based 3D dosimetry system has recently been developed. Such a dosimeter can be used for dose verification in deformed geometries, which requires knowledge of the dosimeter's mechanical properties. In this study we have characterized the dosimeter's elastic behaviour under tensile and compressive stress. In addition, the dose response under strain was determined. It was found that the dosimeter behaved as an incompressible hyperelastic material with a non-linear stress/strain curve and with no observable hysteresis or plastic deformation even at high strains. The volume was found to be constant within a 2% margin at deformations up to 60%. Furthermore, it was observed that the dosimeter returned to its original geometry within a 2% margin when irradiated under stress, and that the change in optical density per centimeter was constant regardless of the strain during irradiation. In conclusion, we have shown that this radiochromic silicone-based dosimeter's mechanical properties make it a viable candidate for dose verification in deformable 3D geometries.